2016
DOI: 10.1038/srep36164
|View full text |Cite
|
Sign up to set email alerts
|

Cassava brown streak virus has a rapidly evolving genome: implications for virus speciation, variability, diagnosis and host resistance

Abstract: Cassava is a major staple food for about 800 million people in the tropics and sub-tropical regions of the world. Production of cassava is significantly hampered by cassava brown streak disease (CBSD), caused by Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV). The disease is suppressing cassava yields in eastern Africa at an alarming rate. Previous studies have documented that CBSV is more devastating than UCBSV because it more readily infects both susceptible and tolerant cass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 53 publications
3
73
2
1
Order By: Relevance
“…The causal viruses of CMD are: African cassava mosaic virus-Kenya (ACMV-K), and East African cassava mosaic virus (EACMV), East African cassava mosaic Zanzibar virus (EACMZV), Uganda variant strain of the EACMV (EACMV-Ug), and East African cassava mosaic Kenya Virus (EACMKV) and for cassava brown streak disease there are two recognized species, Cassava brown streak virus and Uganda cassava brown streak virus with many more being uncovered as more genomes are characterized [14,15]. The challenge now is to match these many viruses of CMD and CBSD with the many species in the Bemisia tabaci species complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causal viruses of CMD are: African cassava mosaic virus-Kenya (ACMV-K), and East African cassava mosaic virus (EACMV), East African cassava mosaic Zanzibar virus (EACMZV), Uganda variant strain of the EACMV (EACMV-Ug), and East African cassava mosaic Kenya Virus (EACMKV) and for cassava brown streak disease there are two recognized species, Cassava brown streak virus and Uganda cassava brown streak virus with many more being uncovered as more genomes are characterized [14,15]. The challenge now is to match these many viruses of CMD and CBSD with the many species in the Bemisia tabaci species complex.…”
Section: Discussionmentioning
confidence: 99%
“…CBSD, on the other hand, is caused by Cassava brown streak virus (CBSV) and Uganda cassava brown streak virus (UCBSV) [11,14]. Recent studies have revealed there are several species of CBSD [14], and CBSD has an accelerated rate of evolution [15]. The disease is characterized by severe chlorosis and necrosis on infected leaves, giving them a yellowish, mottled appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on characterization and evolution of cassava brown streak viruses have revealed different genetic sequences between CBSV and UCBSV, and that genetic diversity is wider among CBSV isolates (Monger et al ., ; Mbanzibwa et al ., ). A recent report suggests that there may be as many as four distinct viral species causing CBSD (Ndunguru et al ., ; Alicai et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The ultimate goal in breeding for cassava resistance to pests is the possibility of developing varieties that have relative resistance to B. tabaci adapted to a wide range of environments (Alicai et al, 2016), forming a basis of an integrated approach to B. tabaci control and ACMD control. The objective of the study focused on assessing genotype × environment interaction (GEI) and Bemisia tabaci effect on tannin, flavonoid, total phenolic concentration and antioxidative capacity.…”
Section: Introductionmentioning
confidence: 99%